2023
DOI: 10.1091/mbc.e23-05-0153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of essential HSF1 reveals an isolated transcriptional stress response selectively induced by protein misfolding

Abstract: Heat Shock Factor 1 (Hsf1) in yeast drives the basal transcription of key proteostasis factors and its activity is induced as part of the core heat shock response. Exploring Hsf1 specific functions has been challenging due to the essential nature of the HSF1 gene and the extensive overlap of target promoters with environmental stress response (ESR) transcription factors Msn2 and Msn4 (Msn2/4). In this study, we constructed a viable hsf1∆ strain by replacing the HSF1 open reading frame with genes that constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…HSF1 is a well-known transcription factor that maintains the cellular proteostasis network in response to the HSR in the cytosol and the UPR in the endoplasmic reticulum [ 22 ]. Thus, we investigated whether HSF1 is closely related to the induction of the expression of HSR- and UPR-related genes in USP7i-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…HSF1 is a well-known transcription factor that maintains the cellular proteostasis network in response to the HSR in the cytosol and the UPR in the endoplasmic reticulum [ 22 ]. Thus, we investigated whether HSF1 is closely related to the induction of the expression of HSR- and UPR-related genes in USP7i-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Matsumoto et al [ 28 ] found that the survival rate of Kluyveromyces marxianus decreased significantly without cell membrane damage, and trehalose was accumulated to eliminate heat–stressed ROS during heat shock at 50 °C for 20 min. It can be seen that the effects of high temperature stress on yeast cells are extensive and comprehensive, and the process of yeast cells adapting to high–temperature heat shock involves the regulation of multiple components such as the cell membrane, proteins and chromatin [ 29 , 30 , 31 ]. At present, we have some understanding of the mechanism of yeast (such as S. cerevisiae and Kluyveromyces marxianus ) adapting to high temperature stress, and most studies have mainly focused on short–term heat shock [ 32 , 33 ], but there are few studies on the mechanism of the high–temperature adaptation of Z. rouxii .…”
Section: Introductionmentioning
confidence: 99%